(untitled) (Al-Farooq Journal of Sciences, 2025)
This study aimed to examine the extent to which job satisfaction influences organizational commitment among academics and employees in Libyan universities. The study employed a descriptive-analytical approach, and data were collected from respondents to investigate the nature of the relationship between job satisfaction and organizational commitment. The study population consisted of all academic staff and employees working in three public universities in Libya: University of Tripoli, University of Zawia, and Sabratha University, with a total population of 12,621 employees. A total of 320 valid questionnaires were collected and analyzed statistically. The study sample was selected using a stratified random sampling technique. Hypothesis testing and path analysis revealed a direct, positive, strong, and statistically acceptable relationship between job satisfaction and organizational commitment among academics and employees in Libyan universities.